Constructing opposition in the age of globalization: the potential of ATTAC - Birchfield, Vicki; Freyberg-Inan, Annette (Globalizations, 2004)
This article examines the movement ATTAC and assesses its potential to function as a vital part of the emerging global opposition to neoliberal globalization. We analyze the agenda of the movement and assess its coherence, both in terms of policy evaluations and prescriptions and in terms of the fit of the movement's organizational structure with its substantive mission and official aims. To this end, we explain the emergence and stellar rise of the movement, compare the particularly successful nation-wide organizations of ATTAC in France and Germany, and examine the movement's transnational activities. We find ATTAC to be coherent in terms of agenda as well as organizational practices and to make a laudable effort to reflect its agenda of democratic empowerment in its political praxis. Acknowledging the enormous challenges faced by transnational civic opposition, we nonetheless conclude optimistically that ATTAC has the potential of serving as a core movement around which such opposition might usefully rally. As a subordinate contribution, our investigation poses the question of how to most usefully conceptualize the nature and role of the movement. We invite scholarly dialogue by locating ATTAC in the context of the study of social movements and transnational civil society and by enriching the theoretical debate on the nature of the emerging global opposition with our empirical observations on one of its main protagonists. Annette Freyberg-Inan is assistant professor at the Political Science Department of the University of Amsterdam. She specializes in the areas of International Relations Theory; International Political Economy and Globalization; European Integration, Democratization and Enlargement; Romanian Politics; Political Psychology; and Methodology. Her most recent publications includeWhat Moves Man: The Realist Theory of International Relations and Its Judgment of Human Nature(New York: SUNY Press, 2004); ‘Organic intellectuals and counter-hegemonic politics in the age of globalisation: the case of ATTAC’, with Vicki Birchfield, in Catherine Eschle and Bice Maiguashca (eds), Critical Theories, World Politics and the ‘Anti-Globalization Movement’(London: Routledge, forthcoming 2005); ‘Transition economies’, in Richard Stubbs and Geoffrey Underhill (eds), Political Economy and the Changing Global Order(Oxford University Press, 3rd ed., forthcoming 2005); Transition, Civil Society, and the Social Sciences in Romania(Stuttgart/Hannover: Ibidem Verlag, forthcoming 2005); ‘World system theory: how the fate of Kosovo reflects the logic and the grip of the world capitalist order’ in Jennifer Sterling-Folker (ed.), Making Sense of IR Theory(Boulder, CO: Lynn Rienner, forthcoming 2005); ‘Which way to progress? The impact of international organizations in Romania’, in Ronald Linden (ed.), Norms and Nannies: The Impact of International Organizations on the Central and East European States(Lanham, MD: Rowman & Littlefield, 2002). Vicki Birchfield is an assistant professor in the School of International Affairs at the Georgia Institute of Technology. Her research interests include comparative and international political economy and European politics. She is currently completing a book manuscript entitledInstitutions, Values and Income Inequality in Capitalist Democraciesand has published articles in theReview of International Political Economy, European Journal of Political Researchand theReview of International Studies.
Political Science
Keywords: ATTAC; globalization; international studies; neoliberalism; social movements

The Continuing 'Wind of Change' in the Balkans: Sources of Housing Inequality in Bulgaria - Vesselinov, Elena (Urban Studies (Routledge), 2004)
The research in this paper explores the institutional changes in the housing system during the period of market transition in Bulgaria, which follow suit with the greater societal transformations. The societal changes are linked theoretically with Polanyi's understanding of the transition from a non-market to a market society. His argument helps in establishing the institutional context of the macroeconomic changes in the past decade. The article then focuses on the changing sources of housing inequality. It is argued that there are two urban regimes of housing inequality: the regime of controlled uniformity during the period of socialism and the regime of primitive diversity during the period of market transition. The two regimes are produced mainly through the changing role of the state.
Sociology; Urban Studies
Keywords: Bulgaria; cities & towns; equality; housing; macroeconomics; socialism; urban studies

Meat for the Multitudes: Market Culture in Paris, New York City, and Mexico City over the Long Nineteenth Century - Horowitz, Roger; Pilcher, Jeffrey M.; Watts, Sydney (American Historical Review, 2004)
Examines an earlier period of oscillation between state intervention and market liberalization in the meat trades of Paris, France New York City, and Mexico City, Mexico. Explanation on market culture; Argument of economic historian Karl Polanyi on the modern capitalist system and market rationality; Discussion on the rules governing the relationship between civil society and state power in the meat trade.
History
Keywords: Mexico; Mexico City; New York; Paris (France); civil society; intervention (federal government); liberalism; market liberalization; meat industry; state intervention

Antecedents of Resistance: Populism and the Possibilities for Democratic Globalization - Plante, David J.; Niemi, William L. (2004)
Globalization is often portrayed as a new and unique phenomenon to our times. However, the dependence of American society upon global markets is not new. American Populists of the 19th century faced a similar matrix of political economic constraints. The Populists faced such challenges as the expansion of international trade, a deflationary international monetary order, integrating global capital markets, dependence on credit, and a political system unable to effectively regulate economic activity to public ends. In short, they responded to a system that from their perspective emphasized corporate profits at the expense of democracy. The Populists goal was to create a more democratic political economy in the face of these constraints. Today globalism has been countered by a diverse series of previously unconnected social movements. This paper argues that these movements are part of a rich tradition of democratic responses to the dislocations resulting from attempts to internationalize and commodify all social relations. As such, these 19th century movements offer instruction in the confrontation between democracy and capitalism in its latest iteration. For example, one important continuity between resistance to globalism today, is the use of democratized traditions of moral economy arguments to confront developing inequalities. Successful fair trade alternatives to free trade similarly depend upon moral economy arguments. Despite the inequalities resulting from globalization, challenges from the democratic promise have endured.
Political Science
Keywords: capital market; capitalism; corporate profits; democracy; fair; globalism; globalization; international trade; monetary policy; populism; trade

Rules of Privatization: Contradictions in Neoliberal Regulation of North Pacific Fisheries - Mansfield, Becky (Annals of the Association of American Geographers, 2004)
Recent changes in fisheries regulation in the U.S. North Pacific reveal how neoliberalism is constituted in practice, and the forms that neoliberalism takes when it engages with environmental management and ecological processes. Whereas neoliberalism can be taken as a political economic philosophy that posits that markets, without state involvement, can best allocate resources, the history and practice of neoliberalism show that it is not as unified as it often appears. Analysis of contemporary fisheries policy reveals not only contradictions in neoliberal approaches, but also how those contradictions are shaped by the environmental context of the industry. This article discusses the rationale for neoliberalism in fisheries and the governance changes enacted in the 1998 American Fisheries Act, which privatized the fishery for Alaska pollock by closing the fishery to all new entrants, providing a set percentage of the yearly catch to “cooperatives” of participants, and allowing individuals to lease their shares. Karl Polanyi's notion of the “double movement” provides a framework to argue that even though regulators tout these reforms because they rely on market mechanisms to resolve recalcitrant ecological and economic problems in these fisheries, writing and implementing the act simultaneously involved complex rule making designed to protect the market. This form of neoliberalism results from the history of fisheries regulation, including recent emphasis on cooperative management, and the ecological characteristics of marine fish. Moves to privatize the oceans entail developing distinctive forms of neoliberal practice that uniquely combine private industry and government regulation. Because fish are one of the last great resource commons, neoliberal approaches to fisheries mark a profound geographical transformation in the political economy of the oceans.
Geography
Keywords: Pacific Ocean; double movement; fishery policy; neoliberalism; privatization

International Relations and the Problem of Difference - Inayatullah, Naeem; Blaney, David L. (Routledge, 2004)
International Relations and the Problem of Difference has developed out of the sense that IR as a discipline does not assess the quality of cultural interactions that shape, and are shaped by, the changing structures and processes of the international system. In this work, the authors re-imagine IR as a uniquely placed site for the study of differences as organized explicitly around the exploration of the relation of wholes and parts and sameness and difference-and always the one in relation to the other. KM: Chapter 5 "Toward an Ethnological IPE" deals extensively with Polanyi's ideas
Political Science
Keywords: economic anthropology; ethnological IPE; international political economy; international relations; political economy

Environmental Values in a Globalizing World: Nature, Justice and Governance - Lowe, Ian; Paavola, Jouni (Routledge, 2004)
This multidisciplinary volume presents a refreshing new approach to environmental values in the global age. it investigates the challenges that globalization poses to traditional environmental values in general as well as in politics and international governance.Divided into five parts, the book investigates how environmental values could be reconceived in a globalizing world.Part I explores contemporary environmental values and their implications for a globalizing world.Part II examines the development of Western and Eastern environmental valuesPart III discusses contemporary environmental politicsPart IV examines how values inform environmental governance and how governance solutions influence which values are realisedPart V concludes the volume with two different views of the prospects of environmental values in a globalising world. This study will be of great interest to students and researchers studying the environment in philosophy, political science, international relations, international environment law, environmental studies and development studies. KM - Contains chapter: "Global Liberalism, Environmentalism, and the Changing Boundaries of the Political : Karl Polanyi's Insights" by John M. Meyer
Political Science
Keywords: MEYER; John M.; environmental policy; globalization; public policy

Globalization, Labor and the 'Polanyi Problem' - Munck, Ronaldo (Labor History, 2004)
This article outlines what the Polanyi problem consists of and provides information on some of the implications that arise in developing a Gramscian/Polanyian strategy of counter-hegemony for the labor and the modern social movements, as of August 2004. Labor and new social movements are allegedly an integral element for a progressive solution of the so-called Polanyi problem, which is how the tendency towards the creation of a global free-market economy can be reconciled with a degree of stability and cohesion in society. Taking a Polanyian perspective allows the development of a historical perspective on the dual transformations of globalization and labor. Towards the end of the Second World War, Karl Polanyi wrote of how a self-regulating market that allegedly could not exist for any length of time without annihilating the human and natural substance of society. Such a utopia would allegedly destroy humanity and transform the world into a wilderness, an opinion mirrored by modern eco-socialists. The strategy and ideology of globalization as transformative revolution seems to echo and confirm Polanyi's account of the 19th century industrial revolution, an attempt to set up a self-regulating market.
Sociology; Political Science
Keywords: GRAMSCI; Antonio; 1891-1937; Polanyi and Gramsci; Polanyi problem; counter-hegemony; economic policy; free enterprise; globalization; international relations; labor movement; labour movement; social movements

Dynamics of Conflict and System Change: The Great Transformation Revisited - Halperin, Sandra (European Journal of International Relations, 2004)
Karl Polanyi's analysis in The Great Transformation has played a prominent role in shaping our understanding of the nature and outcome of both globalization and the movements that have emerged to resist it. However, this article argues that Polanyi's account of the rise and demise of Europe's 19th-century market system is, in important respects, incomplete and misleading. Its central concern is Polanyi's neglect of class structures and processes and how this leads him to mischaracterize both the international and domestic institutions of Europe's 19th-century market system, and the central dynamic driving its development and ultimate collapse. The article critically reviews key features of Polanyi's analysis. Based on this review, it then presents a re-reading of the history of Europe's unregulated market system. Finally, it considers the implications of this alternative account for how we view the context and conditions for globalization and the ways it can best be resisted or shaped in less destructive ways.
Political Science; International Relations
Keywords: Europe; class conflict; globalization; international relations; international trade; markets; organizations and policy; social conflict; transformation; transnational capital

And if there was no state?: critical reflections on Bates, Polanyi and Evans on the role of the state in promoting development - Menocal, Alina Rocha (Third World Quarterly, 2004)
The article review three books about the role of the state in promoting development. It includes "Markets and States in Tropical Africa: The Political Basis of Agricultural Policies," by Robert Bates, "Embedded Autonomy: States and Industrial Transformation," by Peter Evans and "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polanyi.
Political Science; Development Studies
Keywords: BATES; Robert H.; 1942-; EVANS; Peter; 1944-; Embedded Autonomy: States and Industrial Transformation; Great Transformation; The (Book); Markets & States in Tropical Africa: The Political Basis of Agricultural Policies (Book); nonfiction; state development

Economic Sociology’s Legacy to Corporate Governance, 2004 - Kahn, Faith Stevelman (2004)
This paper explores the intellectual tradition of Max Weber,Emil Durkheim, Joseph Shumpeter and Karl Polanyi — economic sociologists whose work has been largely ignored by corporate governance scholars focused on the more traditional areas of economics. The foundation laid by Weber is the central focus of the paper. Weber's writing in Economy and Society laid the groundwork for an approach to the study of firms and markets that diverges significantly from that in of the neoclassical economic model. Weber viewed firms and markets as being deeply embedded in and inseparable from the larger systems of social values and social structures that make a society durable. He grounded his view of economic action in a view of social action. Social actions are all deliberate (meaning purposive, which would include deliberately passive) acts undertaken in contemplation of others' acts and reactions. Transactions in money are generally social actions, since the value of money is determined by what people will decide to give you for it! Economic actions are constantly ormed by patterns of meaning, systems of power and social systems (the family....) that underlie them. From this perspective, the growth of the firm has as much to do with the need for rationalization and the rational/economic division of labor (esp. in a condition of limited liability) as it does with any immediate reduction of transaction costs. Rationality ( the struggle for meaning and systems that order chaos) is as pressing a force as efficiency. Recent writing in economics has come close to building a bridge back to economic sociology, especially with its interest in the effects (or lack of) trust in economic transacting as well as other "behavioral" variations. Economic sociology pursues these departures from qualitative rationality at the level of social structure, rather than individual psychological aberrancy. This paper tries to broader this more "socially" oriented view of the behavior of human beings in firms and markets. This intellectual background is related to contemporary issues in corporate governance legislation, and especially the Sarbanes Oxley reforms and then the increased demand for independent directors at public companies and mutual funds.
Law; Sociology
Keywords: DURKHEIM; Emile; WEBER; Max; 1864-1920; corporate governance; economic sociology; social action; social structure; socioeconomics

'Social Market Economy' as Europe's Social Model? - Joerges, Christian; Roedl, Florian (Social Science Research Network, 2004)
Europe continues to search for its - "European" - social model and the search seems to become increasingly urgent. It is no longer just the "democratic deficit", but also and alongside it, the "social deficit" of the EU which needs to be cured. That new concern is, in fact, a rejection of the older answers. According to the ordo-liberal interpretation of the European legal order as an "Economic Constitution" and, successively, in the analyses of the EU as a "Regulatory State", the sphere of social policy was to remain a domain of the nation state. This seems to have become impossible. The Constitutional Treaty, indeed, makes a new commitment: "The Union shall work for a Social Market Economy". This paper submits that this commitment is conceptually a failure, and politically not credible. The Convention preparing the Constitutional Treaty has apparently ignored the meaning of the concept in the form in which it was shaped in Germany's post-war period. This history entails some pitfalls for the Convention's intentions, as the German "Social Market Economy" involved not only a claim of integrating social concerns into the market economy, but also served to restrict claims for instruments of social policy remarkably at the same time. Moreover, the Convention has failed to confer a new and independent content to the concept of the "Social Market Economy", which could help to overcome the concept's ambivalent history, as well as the Union's real "social deficit". The few innovations, the Charter's Fundamental Social Rights and the Open Method of Co-ordination, were incorporated in such modest and non-committal forms that their potential to further the case for "social Europe" seems marginal. The paper concludes that the invocation of the "Social Market Economy" in the Constitutional Treaty is conceptually flawed and is politically an all too risky promise which may raise expectations which it will subsequently fail to deliver.
Law; Political Science
Keywords: constitution building; economic law; economic policy; governance; social deficit; social market economy; social policy

Agenda 2010: German social democracy and the market state - Thompson, Peter (Debatte, 2004)
Ideology is always for something. Who thought neoliberalism was any different? The post-Cold War provides an excellent laboratory in which to observe 20th c. civilization crumbling, even as it marches towards world markets unbounded by law or social principles. Through repetition and rhetorical sleight-of-hand, the market has robbed the state and thus the polis of its agency. Thus, Schroeder’s SPD is contemplating yet another retreat from the social democratic model, in favor of the post-welfare-state model already well established in the UK and America. And yet within the SPD ranks are breaking as members watch the party abdicate Germany’s basic social contract. These events are reminiscent of M. Polanyi’s The Great Transformation [1744], and they demonstrate once again Marx’s prescience.
Political Science; Germanic Studies
Keywords: Germany; Great Transformation; The (Book); Social Democratic party; markets; social democracy

The third way and the third world: poverty reduction and social inclusion in the rise of 'inclusive' liberalism - Porter, Doug; Craig, David (Review of International Political Economy, 2004)
In the wake of frank neo-liberalism, and in the context of rising security fears, ways are being found to provide market liberalism with a more inclusive face. The Poverty Reduction Strategies currently prominent in international development, and Thirdway OECD 'Social Inclusion' policy frames claim common purpose to promote 'opportunity, empowerment and security' for people and places on the peripheries of global economies and societies. They share commitments to global economic integration and openness, market led growth, 'good' and 'joined up' governance, local and social partnerships, and wide-ranging activation of 'capacities'. But the high rhetorical aspirations of liberalism to social 'inclusivity' have so far overreached empirical gains for the poor. Drawing on developing country examples of Poverty Reduction Strategy and public policy in New Zealand's current Labour government, this paper sketches salient features of 'inclusive' liberalism. It critically examines its status as a Polanyian turn within a wider liberal project, which seeks to re-embed and legitimate a liberal social and economic order.
Sociology; Political Science
Keywords: New Zealand; developing countries; international competition; international political economy; liberalism; political planning; poverty; poverty reduction; self-efficacy; social inclusion; third way

Disembedded Liberalism: Why global - Borowiak, Craig (2004)
Bringing together democratic theory and international political economy literatures, I begin with the thesis that economic globalization is undermining the embedded liberalism of the post WWII era. Embodied in the Keynsian welfare state, embedded liberalism held out democratic avenues for disaffected groups to hold political actors responsible for suffering induced by market forces. Transformations in the global economy, however, constrain the options available to governments and curtail avenues of democratic accountability. Some have argued that the market itself can provide an adequate alternative. This view is deeply flawed. Drawing from the economic theory of Hayek and Friedman, I discuss how markets can operate as accountability mechanisms. I then turn to Karl Polanyi to discuss how markets that become disembedded from social contexts induce severe consequences for society and the environment. These consequences exceed what markets alone can account for. What’s more, as Habermas has observed, the system logic of markets is incompatible with the deliberative contexts in which democratic decision-making takes place. To propose markets as the solution to democratic deficits is to miss the point that it is the substitution of markets for social regulation that generates many of the problems in the first place. It is also to ignore the ways markets undermine the very spaces in which legitimate solutions can be determined. Somehow the effects of market accountability need to be accounted for. For this, there can be no substitute for forms of democratic deliberation that are themselves not reducible to market pressures.
Political Science
Keywords: economics; globalization; international relations; liberalism; markets

'Spatial' relationships? Towards a reconceptualization of embeddedness - Hess, Martin (Progress in Human Geography, 2004)
The concept of embeddedness has gained much prominence in economic geography over the last decade, as much work has been done on the social and organizational foundations of economic activities and regional development. Unlike the original conceptualizations, however, embeddedness is mostly conceived of as a 'spatial' concept related to the local and regional levels of analysis. By revisiting the early literature on embeddedness - in particular the seminal work of Karl Polanyi and Mark Granovetter - and critically engaging with what I will call an 'overterritorialized' concept, a different view on the fundamental categories of embeddedness is proposed. This reconceptualization then is illustrated using the poststructuralist metaphor of a rhizome to interpret the notion of embeddedness and its applicability to different geographical scales.
Geography
Keywords: GRANOVETTER; Mark; associations; cosmography; economic geography; embeddedness; geography; global production networks; institutions; new regionalism; organization; rhizome; social networks; socioeconomics

Student Labor and Evolution of Education - Sidorkin, Alexander M. (World Futures: The Journal of General Evolution, 2004)
The evolution of teaching is examined in three stages: apprenticeship, classical schooling, and mass schooling. All three stages use different social technologies to operate. The mass schooling is analyzed from the point of view of economic anthropology developed by Karl Polanyi, as a non-market economic system. Mass schooling uses the forms of motivation found in archaic, tribal economies: students do their homework and attend school out of considerations of reciprocity. Schools must be treated differently with respect to their improvement. School improvement should be based on perfecting existing non-market economic mechanisms, not on plunging schools into market economy.
Anthropology
Keywords: POLANYI; Karl; 1886-1964; apprenticeship programs; economic anthropology; education; educational anthropology; evolution of education; motivation in education

How likely is a Post-Smithist 21st Century? - Cole, Constance H. (2004)
The current understanding of U.S. hegemony rests on the assumptions of neoclassical theories of both the state and the market. While the service-dominated economy is considered post- Fordist, the rhetoric of the state focuses on institutions of democracy. To what extent is our understanding of democracy dependent on the prior assumptions that the economy is ‘free’? If we reexamine the assumptions about the links between state and economy, drawing on the work of Gramsci, and Polanyi the necessary link between state and economy assumed in our current neoclassical theory looks quite different. The thesis of this research is that hegemonic ideologies of the relationship of state and market reinforce the interests of the commercial class at the expense of any meaningful representation of the working classes. Reconceptualizing the links between state and market in terms of an economics subordinate to social relations beyond those of commercial interests indicates the possibilities of a ‘post- Smithist’ understanding of both the imperfections of neoclassical market theories, and of the narrowness of institutional analyses.
Political Science; International Studies
Keywords: Fordism; Smithism; United States; democracy; economics; economy; hegemony; international; political; post; theory

The Culture War Goes Global: 'Family Values' and the Shape of U.S. Foreign Policy - Kline, Scott (2004)
Examines a neoconservative-religious right nexus that has emerged in and around the Bush White House. Discussion on the work of Karl Polanyi to examine a paradoxical tension that exists between U.S. nationalism and the promotion of a free-market economy; Family values nationalism and free market capitalism; Proposed two areas of critique that have been influenced by the work of Christian realists.
Politcal Science
Keywords: United States; capitalism; economic policy; free enterprise; international studies; nationalism; neo-conservatism; political doctrines

The Reconfiguration of the State under Economic Conditionality and the Creation of Hollow Democracies ? With Illustrations from Zambia - Lloyd, Peter (2004)
This paper will explore the linkages and contradictions between the promotion of democracy and the application of economic and political conditionality in Southern Africa, with particular reference to Zambia. Many electoral democracies have emerged in Africa in the last decade in conjunction with and partially as a consequence of the conditions applied to loans by bilateral and multilateral donors. It will be argued that the process of conditionality and the neoliberal policies applied actually inhibit the emergence of substantive democracy and present a threat to the consolidation and longevity of even minimal forms of liberal democracy. The conditions applied to aid represent an attempt to reconfigure the activities, capacity and capabilities of the state. Most significantly, they involve the imposition of a neoliberal economic model which is seen as technically necessary to tackle economic crisis and which due to the leverage offered donors by the indebtedness of recipient countries is uncontestable, yet require active state intervention to achieve (Polanyi’s insight that the creation of self regulating markets require regulatory state activity). A major area of state policy is thus placed beyond accountability to the electorate of the recipient country; this is also true of many aspects of political and social policy. The process of negotiation between the International Financial Institutions and representatives of countries (most often the President and a small group of politicians and advisors from the finance ministry) also promotes a concentration of power within the state as representatives must be able to adopt positions on the behalf of their country and enact agreed policies from the top down. Conditionality thus involves a reduction in the democratic accountability of the state in three ways: Firstly, as political authority shifts upwards to the international sphere, to the IFIs and donor community; secondly as power is centralised within the presidency and finance ministry; thirdly, the scope of democracy is limited as liberalisation and the strict separation of politics and economics are enforced, placing many elements of economic life beyond the reach of democratic institutions. Applying this framework to Zambia, it will be argued that consequently a very limited and hollow form of democracy where most of the important political and economic processes affecting people’s lives are unaccountable to them has been created, and that increasing disillusionment and political volatility are ensuing, possibly representing a threat to even this minimal democracy.
Political Science
Keywords: South Africa; democracy; economics; international studies; political doctrines; political science

Endogenous Preferences and Embeddedness: A Reappraisal of Karl Polanyi - Rodrigues, João (Journal of Economic Issues (Association for Evolutionary Economics), 2004)
This article examines the relevance of the Karl Polanyi's contributions to economics in general and to the issue of endogeneity of human preferences in particular. Although Polanyi never spoke of endogenous preferences, one can capture in his work a vision of the historical specificity and institutional dependence of human purposes and reasons for behavior. It is undeniable that in Polanyi there is a certain tendency to overlook human volition and to fall into a kind of institutional determinism. Nevertheless Polanyi recognizes the scope for deliberate human action when he defines institutions as the embodiments of human meaning and purposes. Furthermore, in Polanyi's work, there is a very clear awareness of the complexity of the motives for human action and a defense, which is continuously reaffirmed, of the plurality of reasons to act in economic interactions and their relation to the patterns of interaction that are dominant. Nevertheless, there is a lack of a clear and well-systematized account of the possible causal links by which institutions influence human preferences. His substantive economy takes morality into account, in the sense that its foundations lie on the recognition that man is a moral being with duties toward himself and others, with an understanding of what is good and what is bad and that these moral codes exert a powerful influence upon economic affairs.
Economics
Keywords: economic anthropology; embeddedness; endogenous preferences; ethics; human behavior; institutional economics; social sciences

Third Worldism and the lineages of global fascism: the regrouping of the global South in the neoliberal era - Patel, Rajeev; McMichael, Philip (Third World Quarterly, 2004)
We come to an analysis of Third Worldism through an historical understanding of the development project, one that locates Third Worldism as a moment in a broader series of resistances both to capital and colonialism, and to the techniques used by the state to maintain hegemony. Viewing Third Worldism in this wider context, we argue, enables us to not only explain the failure of Third Worldism to deliver on its vision of emancipation from colonialism, but to also explain the shape of contemporary resistance to the world capitalist order. We argue that the theory and practice of development depends on a certain biopolitics, rooted in a regime of sovereign state control, and designed to mobilise citizens in ways favourable to capital. We hold that Third Worldism embraced this form of sovereignty and its biopolitics. Further, by blending cultural studies analysis with a Polanyian interpretation of the rise of fascism, we argue that Third Worldism can be situated as a moment in the maturation of 'global fascism'. Finally, we argue that contemporary resistances to neoliberalism have recognised the complicity of the state with capital. These 'new internationalisms' arise from the ashes of Third Worldism, with an altered understanding of 'sovereignty' that challenges the trajectory of the Third World sovereign state.
Sociology; Development Studies
Keywords: biopolitics (sociobiology); capitalism; colonies; fascism; global capital; global fascism; hegemony; liberty; sovereignty (political science)

Social Exclusion in a Comparative Context - Reimer, Bill (Sociologia Ruralis, 2004)
This paper outlines a framework for understanding social exclusion that is multidimensional, dynamic, multi-leveled, and relational. Inspired by Polanyi's classification of the modes of economic inclusion, we propose that social inclusion and exclusion processes are rooted in four types of social relations: market (exchange and barter), bureaucratic (rational-legal), associative (common interest), and communal (complex reciprocity and shared identity). Each type reflects different, but integrated processes of social exclusion and inclusion. These four types are outlined conceptually, then operationalized using data from a Canadian survey conducted in 1995 rural households. The results show the extent to which the four types of relations are used for social support, their interdependence, and their relationship to selected household characteristics and outcomes. The policy implications discussed emphasize the ways in which building capacity in all four types of relations can increase the level of social inclusion.
Sociology
Keywords: Canada; economic inclusion; rural sociology; social exclusion

Debt Abides: A Prolegomena for Any Future Chapter 11 - Ayer, John D. (American Bankruptcy Law Journal, 2004)
This article presents information related to market transactions. As a mode of organization, markets are so pervasive in our own lives that it may be hard to think just how novel and contingent (in geologic time) they may be. It was economist Karl Polanyi who sought to isolate a juncture in this process of "becoming a market", the point at which the idea of the market transaction becomes not just a tool or an instrument, but a central organizing principle of social life. But it is not clear that even Polanyi would have been able to conceive a later stage, a stage in which the market becomes not merely a tool of the firm or an expression of sovereignty, but a substitute for the firm and for sovereignty itself.
Law; Political Science
Keywords: autonomy (Political science); international law; markets; organization; political science; social interaction

The Great Transformation in Understanding Polanyi: Reply to Hejeebu and McCloskey - Blyth, Mark (Critical Review, 2004)
Santhi Hejeebu and Deirdre McCloskey's rebuttal to Karl Polanyi's Great Transformation begs several important questions. Yes, commerce can be found throughout human history–but is that the same as saying that people have been equally capitalistic at all times? If not, then how did modern capitalism come into being? Hejeebu and McCloskey portray capitalism as having evolved gradually, indeed quite naturally, rather than being a contingent product of politics. Not inconsistently, Hejeebu and McCloskey radically distinguish between what people "think" and what they "do"–that is, between their ideas and their actions. This distinction, too, suggests that human action is ahistorically capitalistic–whatever human agents at different times and places might think.
Political Science
Keywords: Hejeebu; McCloskey; economic thought; history; modern capitalism

Pinochet meets Polanyi? The Curious Case of the Chilean Embrace of "Free" Market Economics - Cypher, Jame M. (Journal of Economic Issues, 2004)
This article argues, within the context of Karl Polanyi's work, that the common view of Chile is doubly miscontrued, in terms of free market economics. Events since the end of the dictatorship (1989) tend to confirm Polanyi's hypothesis in 'The Great Transformation' (1957; discussed in the following section) while at the same time negating the Chicago School's view that a free market society could be built–even under a dictatorship. In Chile from September 1973 onward through 1989, the Chicago School–inspired economists known as the Chicago Boys, engaged in what would appear to be the most determined utopian endeavor of economic liberalism to set up a self-regulating market system. It is the hypothesis of this paper that the Chicago School failed spectacularly in this effort and that the credit they have widely received for successfully remaking the Chilean economy properly belongs to the antithesis of the Chicago School–successful state-led efforts to restructure the economy and foster development. Far from the fictitious utopia of the free market, under the dictatorship the state was also heavily involved in projects designed to massively transfer economic rents to the private sector. Consistent with Polanyi's thesis, the Chicago School was able to drastically reduce Chile's social legislation, labor legislation, and social controls over the exploitation of the natural resources of Chile only within the context of a military dictatorship. While Chile's elected governments have embraced the Chicago School's faith in unlimited and unregulated free international trade, in the area of social legislation and labor legislation there are very strong indications that civil society is systematically and effectively striving to overcome the retrograde steps imposed by the dictatorship.
Economics
Keywords: Chicago school of economics; Chile; economic conditions; economics; free enterprise; politics and government

Heilbroner and Polanyi: A Shared Vision - Dimand, Robert W. (Social Research, 2004)
The article presents the shared vision of Polanyi and Heilbroner. This paper focuses on the parallel ideas of economists Karl Polanyi and Robert Heilbroner. Their concept on the role of market system in the emergence of economics as a field of study is explained. More issues included are the requirements for the transformation of a pre-market society into a true market, Polanyi's influence to several economists, and relevance of the Polanyi/Heilbroner vision of the market system to the postcommunist countries transition to the market.
Economics
Keywords: HEILBRONER; Robert; economics; economics - statistical methods; economists; markets; social sciences; societies; statistics

Re-Inventing Karl Polanyi: On the Contradictory Interpretations of Social Protectionism - Drahokoupil, Jan (Sociologický Časopis / Czech Sociological Review, 2004)
The ideas of Karl Polanyi's The Great Transformation have often been referred to in the recent debates that have emerged as a reaction to the rise of neoliberal policies. This paper deals with contradictory interpretations of the notion of social protectionism in the work of Karl Polanyi. There are two opposing interpretations distinguished here. The first interprets social protectionism as a balancing principle of economic liberalism. The second understands social protectionism as a part of market pathology. In order to assess the validity of competing interpretations, the author puts forth an account of social protectionism in the context of Polanyi's theory of the economy and society. The author concludes that the popular notion of social protectionism as a balancing principle of economic liberalism does not correspond to Polanyi's theory. In addition, the author offers a skeptical commentary on the utility of Polanyi for understanding social protectionism in social analysis.
Sociology; Economics
Keywords: critique; social protectionism

War and Social Change in Modern Europe: The Great Transformation Revisited - Halperin, Sandra (Cambridge University Press, 2004)
Halperin traces the persistence of traditional class structures during the development of industrial capitalism in Europe, and the way in which these structures shaped states and state behavior and generated conflict. She documents European conflicts between 1789 and 1914, including small and medium scale conflicts often ignored by researchers and links these conflicts to structures characteristic of industrial capitalist development in Europe before 1945. This book revisits the historical terrain of Karl Polanyi's The Great Transformation (1944), however, it argues that Polanyi's analysis is, in important ways, inaccurate and misleading. Ultimately, the book shows how and why the conflicts both culminated in the world wars and brought about a 'great transformation' in Europe. Its account of this period challenges not only Polanyi's analysis, but a variety of influential perspectives on nationalism, development, conflict, international systems change, and globalization.
Political Science
Keywords: Europe; history; international relations; political science - history and theory

Polanyi and the History of Capitalism: Rejoinder to Blyth - Hejeebu, Santhi; McCloskey, Deirdre (Critical Review, 2004)
Mark Blyth's rebuttal to our constructive critique of Polanyi "blithely" takes for granted the accuracy of Polanyi's now-outdated historiography of capitalism–by means of a loose, overly expansive definition of capitalism that question-beggingly equates it with modernity. Blyth emphasizes the need to view markets as "socially embedded," with which we agree–but he appears not to take account of the individual self-interest that is thus embedded. Similarly, he asserts a priori the role of ideas in history, in parallel to the economists he condemns (unfairly) for reading ideas out of history a priori. All of this poorly serves the cause of extracting Polanyi's welcome emphasis on social embeddedness and on the empirical from the ideological and methodological certitudes and errors in which The Great Transformation placed them.
Economics
Keywords: BLYTH; Mark; history of economic thought: individuals

The Meaning of Freedom in a Complex Society: The Development of Karl Polanyi's Thought on Economics, Modernity, and Human Liberty - Katsh, Gabriel (Harvard University, 2004)
Political Science
Keywords: freedom in a complex society

Desolation and Enlightenment: Political Knowledge After Total War, Totalitarianism, and the Holocaust - Katznelson, Ira (Columbia University Press, 2004)
During and especially after the Second World War, a group of leading scholars who had been perilously close to the war's devastation joined others fortunate enough to have been protected by distance in an effort to redefine and reinvigorate Western liberal ideals for a radically new age. Treating evil as an analytical category, they sought to discover the sources of twentieth-century horror and the potentialities of the modern state in the wake of western desolation. In the process, they devised strikingly new ways to understand politics, sociology and history that reverberate still. In this major intellectual history, Ira Katznelson examines the works of Hannah Arendt, Robert Dahl, Richard Hofstadter, Harold Lasswell, Charles Lindblom, Karl Polanyi, and David Truman, detailing their engagement with the larger project of reclaiming the West's moral bearing. In light of their epoch's calamities these intellectuals insisted that the tradition of Enlightenment thought required a new realism, a good deal of renovation, and much recommitment. This array of historians, political philosophers, and social scientists understood that a simple reassertion of liberal modernism had been made radically insufficient by the enormities and moral catastrophes of war, totalitarianism, and holocaust. Confronting their period's dashed hopes for reason and knowledge, they asked not just whether the Enlightenment should define modernity, but which Enlightenment we should wish to have. Decades later, in the midst of a new type of war and reanimated discussions of the concept of evil, we share no small stake in assessing their successes and limitations.
Sociology; Political Science
Keywords: ARENDT; Hannah; World War II; fascism; military history; political history; political philosophy; political theory; totalitarianism

Polanyi Symposium: a conversation on embeddedness - Krippner, Greta; Granovetter, Mark; Block, Fred; Biggart, Nicole; Beamish, Tom; Hsing, Youtien; Hart, Gillian; Arrighi, Giovanni; Mendell, Margie; Hall, John; Burawoy, Michael; Vogel, Steve; et al. (Socio-Economic Review (2004), 2004)
This conversation, transcribed from a conference in April 2002, is intended to illuminate current debates about the use and abuse of the embeddedness concept in economic sociology.
Sociology
Keywords: economic sociology; embeddedness; markets; symposium

Building a Solidarity Economy in the 21st Century - Lewis, Mike; Conaty, Patrick (Newsletter of the North American Network for the Solidarity Economy, 2004)
"If we don't set out a stronger theoretical base for our work, if the movements we build are simply pragmatic & without a sound intellectual base, we will not succeed in changing hearts and minds." Pat Conaty
N/A
Keywords: solidarity economy

Global liberalism, environmentalism and the changing boundaries of the political: Karl Polanyi's insights - Meyer, J.M. (Environmental Values in a Globalizing World: Nature, Justice and Governance, 2004)
Political Science
Keywords: environmentalism; global liberalism

Changing employment protection systems : Karl Polanyi's "Double Movement" and the evolution of federal labour standards in Australia 1979 to 2000 - Michelotti, Marco (Association of Industrial Relations Academics of Australia and New Zealand, 2004)
Yes
Management Studies; Business Studies
Keywords: Australia; double movement; industrial relations; labour standards

Globalization: People, Perspectives, and Progress - Mott, William H. (Greenwood Publishing Group, 2004)
This study expands the narrow economic-commercial focus of the topical media and places globalization in a multidisciplinary context as a continuing process and a permanent condition that transforms human living and society. Early chapters review the development of globalization as creating and diffusing knowledge, expanding people's perspectives on living, and continuing progress. These chapters introduce globalization as an iterative, human, and deliberate process of creating new knowledge and using it to reinterpret the world, time, and man's place in both. The later chapters present the major analytical perspectives of globalization–political, cultural, and economic–and a comparison of the primary carriers of globalism and barriers to globalization.Drawing on classical and modern analysis, as well as narrow, topical journalism, the work focuses each perspective on people through the human processes of creating knowledge and living together. The work expands the economic perspective beyond the fashionable focus on trade and investment into the triggering and shadowing relationships between economic growth, political conflict, and social stress. The political perspective expands international politics and law to global governance, triadic dispute resolution, and global civil society. The cultural and antiglobal perspectives reflect the success of economic globalization in bringing people directly into the narrowly rational processes of international politics and economics. The final analytical chapter collects and compares observations and develops conclusions about globalization across the several perspectives. Speculation about alterative futures for globalizing humanity can constitute a coherent standard, ideal, or direction for policymaking, or an agenda for continuing research and debate.
Political Science
Keywords: comparative politics; political science; social science

Sustainable Development and the North American Free Trade Agreement: A Polanyian Interpretation - Plante, David J (University of Utah, 2004)
Political Science
Keywords: economic integration; environment and development; environment and trade; environmental accounts and accounting; environmental equity; population growth; sustainability; sustainable development; thesis; trade and environment